Simulierte Online-Beratung : Fallbeispiel Maria - Honervogt, Johannes; Zenker, Sven; Holmes, Scott; Holmes, Scott; Kreutz, Paul; Kreutz, Paul (AWO Kreisverband Bielefeld e.V., 2021)
Mit diesem Video wird eine online Beratung simuliert.